2009
DOI: 10.3892/ijo_00000208
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of periostin may help identify patients with more aggressive colorectal cancer

Abstract: Abstract. Elevated levels of periostin have been implicated as playing important roles in tumor invasion and metastasis in various tissues. Thus, we determined whether serum periostin levels were associated with progression and poor prognosis in colorectal cancer (CRC) patients. We measured serum periostin levels by ELISA in 67 CRC patients and 120 controls. We also evaluated periostin expression in human CRC specimens (n=15) using immunohistochemistry, and measured expression of periostin mRNA in 7 CRC tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…We validated that high expression of SPOCK1 and POSTN was associated with the poor prognosis of CRC patients by applying OS and DFS analyses based on GEPIA and GSE17536. This is consistent with previous studies on POSTN [25,26] , but the prognostic value of SPOCK1 in CRC has not been reported before. Besides, high expression of SPOCK1 and POSTN was correlated to higher clinical stage, T stage, and N stage, but not with M stage, which is consistent with the WGCNA analysis.…”
Section: Discussionsupporting
confidence: 93%
“…We validated that high expression of SPOCK1 and POSTN was associated with the poor prognosis of CRC patients by applying OS and DFS analyses based on GEPIA and GSE17536. This is consistent with previous studies on POSTN [25,26] , but the prognostic value of SPOCK1 in CRC has not been reported before. Besides, high expression of SPOCK1 and POSTN was correlated to higher clinical stage, T stage, and N stage, but not with M stage, which is consistent with the WGCNA analysis.…”
Section: Discussionsupporting
confidence: 93%
“…We validated that high expression of SPOCK1 and POSTN was associated with the poor prognosis of CRC patients by applying OS and DFS analyses based on GEPIA and GSE17536. This is consistent with previous studies on POSTN [25,26] , but the prognostic value of SPOCK1 in CRC has not been reported before. Besides, high expression of SPOCK1 and POSTN was correlated to higher clinical stage, T stage, and N stage, but not with M stage, which is consistent with the WGCNA analysis.…”
Section: Discussionsupporting
confidence: 93%
“… 28 One study has even found serum levels of POSTN in patients correlated with primary CRC mRNA expression as well as the risk of distant metastasis. 29 …”
Section: Discussionmentioning
confidence: 99%